“A Study of Equity Mutual Funds in India in Terms of Risk-Adjusted Performance and Selection and Timing Ability of Fund Managers” - Jain, Sukrita (2014)
This paper evaluates the performance of 54 Indian equity mutual funds for the period 7th January 2010-1st January 2014 by employing traditional one parameter performance measures like Sharpe ratio, Treynor ratio and Jenson’s Alpha. Additionally, the study also tries to evaluate the stock selection and market timing ability of the mutual fund managers. This is done by employing the Treynor- Mazuy and Henriksson and Merton models. The results indicate poor performance of most mutual funds in terms of single parameter measures and the inability to outperform the market indices (CNX NIFTY and S&P BSE 200). The Treynor Mazuy model indicates poor stock selection ability and wrong market timing while the Henriksson and Merton model indicates good stock selection ability of most funds but wrong market timing in respect to the benchmarks. However this study has its own limitations and if these are corrected for, the results produced may be altered.